2006
DOI: 10.2353/ajpath.2006.050752
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal or Glial Expression of Human Apolipoprotein E4 Affects Parenchymal and Vascular Amyloid Pathology Differentially in Different Brain Regions of Double- and Triple-Transgenic Mice

Abstract: Apolipoprotein E4 (ApoE4) is associated with Alzheimer's disease by unknown mechanisms. We generated six transgenic mice strains expressing human ApoE4 in combination with mutant amyloid precursor protein (APP) and mutant presenilin-1 (PS1) in single-, double-, or triple-transgenic combinations. Diffuse, but not dense, amyloid plaque-load in subiculum and cortex was increased by neuronal but not glial ApoE4 in old (15 months) double-transgenic mice, whereas both diffuse and dense plaques formed in thalamus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 72 publications
3
23
0
Order By: Relevance
“…In A␤PP and PS1 Tg mice, the thalamic deposition of vascular amyloid is mediated by glial Apo E expression. 34 Our observations indicate that in the Tg-SwDI mice there is an intimate association between vascular amyloid deposits and Apo E. Furthermore, the lack of endogenous mouse Apo E, as in the Tg-SwDI with Apo E knockout mice, severely reduces thalamic microvascular amyloid deposition. 35 Interestingly, the C57BL/6 mouse, the background strain used in this study, appears to be more susceptible to age-dependent atherosclerosis and arteriosclerosis than other mice.…”
Section: Discussionmentioning
confidence: 72%
“…In A␤PP and PS1 Tg mice, the thalamic deposition of vascular amyloid is mediated by glial Apo E expression. 34 Our observations indicate that in the Tg-SwDI mice there is an intimate association between vascular amyloid deposits and Apo E. Furthermore, the lack of endogenous mouse Apo E, as in the Tg-SwDI with Apo E knockout mice, severely reduces thalamic microvascular amyloid deposition. 35 Interestingly, the C57BL/6 mouse, the background strain used in this study, appears to be more susceptible to age-dependent atherosclerosis and arteriosclerosis than other mice.…”
Section: Discussionmentioning
confidence: 72%
“…This is a surprising result given that A␤40 is reported to be the predominant A␤ species deposited in vessels (Gravina et al, 1995). Although previous studies suggested that a higher ratio of A␤40 to A␤42 might promote the formation of CAA over parenchymal deposition (Herzig et al, 2004;, in other studies, selective increases in A␤42 were associated with more CAA (Van Dorpe et al, 2000;Samura et al, 2006;Van Dooren et al, 2006). Our previous studies showed that high-level production of wild-type A␤40 by itself is not sufficient to cause CAA .…”
Section: Discussionmentioning
confidence: 95%
“…Experimental manipulations such as co-expressing human apoE4 with APPswe (48), or introducing the E693Q Dutch mutation into APP transgenic mice (49), both elevated the ratio of A␤40:42 and caused redistribution of amyloid deposits from the parenchyma to the vasculature. Conversely, several experiments designed to specifically lower the production of A␤40 relative to A␤42, such as co-expressing mutant PS1 with APP (50,51) or expressing an A␤42-exclusive transgene (52), are also reported to increase cerebral amyloid angiopathy in transgenic mice. Our current results are most consistent with the hypothesis that lowering A␤40:42 increases the appearance of vascular amyloid.…”
Section: Discussionmentioning
confidence: 99%